Fatty Acid Esters of Hydroxy Fatty Acids (FAHFAs) Are Associated With Diet, BMI, and Age - Kellerer, Teresa; Kleigrewe, Karin; Brandl, Beate; Hofmann, Thomas; Hauner, Hans; Skurk, Thomas (Frontiers in Nutrition, 2021)
Background: Fatty acid esters of hydroxy fatty acids (FAHFAs) are a group of fatty acids with potential anti-inflammatory and anti-diabetic effects. The blood levels of FAHFAs and their regulation in humans have hardly been studied. Objective: We aimed to investigate serum FAHFA levels in well-characterized human cohorts, to evaluate associations with age, sex, BMI, weight loss, diabetic status, and diet. Methods: We analyzed levels of stearic-acid-9-hydroxy-stearic-acid (9-SAHSA), oleic-acid-9-hydroxy-stearic-acid (9-OAHSA) and palmitic-acid-9-hydroxy-palmitic-acid (9-PAHPA) as well as different palmitic acid-hydroxy-stearic-acids (PAHSAs) by HPLC-MS/MS with the use of an internal standard in various cohorts: A cohort of different age groups (18–25y; 40–65y; 75–85y; Σn=60); severely obese patients undergoing bariatric surgery and non-obese controls (Σn=36); obese patients with and without diabetes (Σn=20); vegetarians/vegans (n=10) and omnivores (n=9); and young men before and after acute overfeeding with saturated fatty acids (SFA) (n=15). Results: Omnivores had substantially higher FAHFA levels than vegetarians/vegans (median (25th percentile; 75th percentile) tFAHFAs = 12.82 (7.57; 14.86) vs. 5.86 (5.10; 6.71) nmol/L; P<0.05). Dietary overfeeding by supplementation of SFAs caused a significant increase within one week (median tFAHFAs = 4.31 (3.31; 5.27) vs. 6.96 (6.50; 7.76) nmol/L; P<0.001). Moreover, obese patients had lower FAHFA levels than non-obese controls (median tFAHFAs = 3.24 (2.80; 4.30) vs. 5.22 (4.18; 7.46) nmol/L; P<0.01) and surgery-induced weight loss increased 9 OAHSA level while other FAHFAs were not affected. Furthermore, significant differences in some FAHFA levels were found between adolescents and adults or elderly, while no differences between sexes and between diabetic and non-diabetic individuals were detected. Conclusions: FAHFA serum levels are strongly affected by high SFA intake and reduced in severe obesity. Age also may influence FAHFA levels, whereas there was no detectable relation with sex and diabetic status. The physiological role of FAHFAs in humans remains to be better elucidated. Trial registration: All studies referring to these analyses were registered in the German Clinical Trial Register (https://www.drks.de/drks_web/) with the numbers DRKS00009008, DRKS00010133, DRKS00006211, and DRKS00009797.